UPAYA INTENSIFIKASI PEMBANGUNAN INDUSTRI PERTAHANAN MARITIM DALAM MENGHADAPI ERA GLOBAL - Yunda Karyawanto; Ari Artanto (Journal of Industrial Engineering & Management Research, 2022)
This study aims to understand the condition of global maritime defense and the efforts that can be made by Indonesia to build a strong and sustainable maritime defense industry. The defense industry requires different policies, regulations, actions and operations from conventional defense strategies. The maritime defense industry is an important key for Indonesia to further increase its strength to protect a sovereign Indonesian region. This study use a qualitative design perspective which is validated through a triangulation process. The results of this study indicate that the dynamics of global political conditions in various regions are very diverse and efforts to control the area of a particular country are important, so it is important for a major country Indonesia to build a maritime industrial defense to provide an adequate supply of defense and security tools in preparing themselves to face the threats. This is a special concern for the government to encourage the development of maritime defense in accordance with the interests of the times in the global era.